Non-Rational Speech of the Cyclops: Rhetorical and Political Aspects Within this Myth - Castro Delgado, Gilberto (2020)
The aim of this paper is the study of the manner how the Cyclops Polyphemus spoke and then we could obtain a kind of social communicative stuff within apolitical statements. This is, although the Cyclops had a language trough out he communicates, he did not possess a notable speech proper of a modern society with their particular lows and the skills of a productive speech which belong to the men who lives social conditions as a common political unity, such as the philosophical ideas from Plato and Aristotle. So this is, Polyphemus and Odysseus are in an antithetical position.